PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN INDRAGIRI HILIR - jurnalmap map; Dian Anggraini; Hadi Susanto; Sutarji ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT Performance of employees relates to the quality and quantity of a job performed by employees or subordinates and related to the condition of a subordinate or employee in a particular organization. For that reason, it would be necessary to analyze by knowing the influence of individual characteristics, work characteristics and work environment that significantly affect the Performance of Employees at the Office of Investment and Integrated Services One Door (DPMPTSP) Indragiri Hilir Regency Researchers in this case focuses on 3 (three) variables to improve employee performance that is: Influence Characteristic Individual, Characteristic Of Work And Work Environment. Keywords: Individual Characteristics, Job Characteristics, Work Environment and Performance